PEMERINGKATAN OBLIGASI: RISET GAP FAKTOR PENENTU RATING OBLIGASI (Fokus Ekonomi, 2009)
Bond rating is a guide to investor who intends to buy bond because that rating gives information statement and giving signal about company’s debt failure possibility. There are previous research show that financial ratio can use to predict bond rating, but still have the difference result. And then, non financial factor not more used by the researcher. This is mind there are gap research  about bond rating because in normative concept there are two factors are financial factor and non financial factor. The purpose of this research are analysis two factor, financial factor and non financial factor to predict bond rating. Analysis  based from a lot of previous empirical research.